Transmesocolic robotic extended pyelolithotomy of a large gas-containing renal stone: Case report and review of the literature - Manny, Ted B. (Medknow Publications & Media Pvt Ltd, 2013)
We present the fifth case in the world literature of a gas-containing urinary stone. Our patient is a 31-year-old woman referred for left flank pain and gross hematuria who was noted on imaging to have a 6.5 cm left renal pelvis stone containing gas. Cultures revealed Escherichia coli from the urine and stone material. Chemistry revealed underlying gouty diathesis. The stone was removed using robotic extended pyelolithotomy. Overall, renal function remained unchanged while drainage improved on nucleotide renography. Review of the world literature suggests that gas-containing renal stones are invariably associated with emphysematous pyelonephritis commonly caused by E. coli and Klebsiella. Contributing factors to gas-containing stone formation include urinary stasis, metabolic mineral derangement and, in a minority of the cases, diabetes.